Recommendations for Plankton Measurements on OceanSITES Moorings With Relevance to Other Observing Sites - Boss, Emmanuel; Waite, Anya M.; Karstensen, Johannes; Trull, Tom; Muller-Karger, Frank; Sosik, Heidi M.; Uitz, Julia; Acinas, Silvia G.; Fennel, Katja; Berman-Frank, Ilana; Thomalla, Sandy; Yamazaki, Hidekatsu; et al. (Frontiers in Marine Science, 2022)
Measuring plankton and associated variables on ocean time-series sites has the potential to revolutionize our understanding of ocean biology and its ties to ocean biogeochemistry by opening temporal scales (e.g., resolving diel cycles) not typically sampled as a function of depth. We focus primarily on the OceanSITES program as it is the largest network of long-term open-ocean time-series stations. In this review we motivate the addition of biological measurements to time-series sites by detailing science questions they could help address, reviewing existing technology that could be deployed to do so, and providing examples of time-series sites already deploying some of those technologies. We emphasize data management aspects as these are critical to maximize the utility of such data and wrap-up with a recommendation for an implementation plan.